2007
DOI: 10.1590/s0074-02762007000100013
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma is required for the late but not early control of Leishmania amazonensis infection in C57Bl/6 mice

Abstract: The critical role of interferon-gamma (IFN-γ) in the resistance of C57Bl/6 mice to Leishmania major is widely established but its role in the relative resistance of these animals to L. amazonensis infection is still not clear. In this work we use C57Bl/6 mice congenitally deficient in the IFN-γ gene (IFN-γ KO) Leishmaniasis is a complex of diseases caused by the obligate intracellular protozoan parasites of the genus Leishmania. The various clinical forms of human leishmaniasis have been partially reproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
1
37
0
1
Order By: Relevance
“…The data are representative of 2 independent experiments. in vivo (Pinheiro and Rossi-Bergmann 2007), and the administration of recombinant IFN-g was not sufficient to induce protection from this parasite in BALB/c mice (Barral-Netto and others 1996). Moreover, the induction of a stronger level of Th1 polarization in a vaccine-treated experimental model (Carneiro and others 2014) or in IL-10-deficient mice ( Jones and others 2002) failed to reverse their susceptibility to this parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data are representative of 2 independent experiments. in vivo (Pinheiro and Rossi-Bergmann 2007), and the administration of recombinant IFN-g was not sufficient to induce protection from this parasite in BALB/c mice (Barral-Netto and others 1996). Moreover, the induction of a stronger level of Th1 polarization in a vaccine-treated experimental model (Carneiro and others 2014) or in IL-10-deficient mice ( Jones and others 2002) failed to reverse their susceptibility to this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments showed that IFNg stimulated the replication of the amastigote forms of the parasite in macrophages instead of killing them (Qi and others 2004). Additionally, during in vivo infections, IFN-g was not required for protection during the early stages of infection (Pinheiro and Rossi-Bergmann 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Indeed many stimuli for VEGF production have been identified which could be involved in leishmanial infection, including hypoxia, HIFs, cytokines and nitric oxide (NO) [18,50,66]. Of relevance to this work is the cytokine interferon-c (IFNc) [52], which is associated with host resistance to Leishmania [3], and produced by C57BL/6 mice infected with L. amazonensis [10,49]. In addition, endogenous NO enhances VEGF synthesis in in vitro models, including macrophages [52,66], and is associated with control of leishmaniasis, since high levels of NO are known to be leishmanicidal and are continuously produced by C57BL/6 mice infected with L. amazonensis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The low IFN-γ production is, in our experience, at least partially responsible for the maintenance of parasites in tissues. Although IFN-γ has been shown to favor growth of L. amazonensis amastigotes in macrophages in vitro and in vivo (Qi et al 2004), this cytokine seems to participate in the late control of L. amazonensis (Pinheiro & Rossi-Bergmann 2007). Moreover, when IFN-γ production is elevated by vaccination, a small but significant decrease in parasite levels is seen (Vanloubbeeck & Jones 2004, Hernández et al 2006, Hernández Sanabria et al 2007, González-Lombana et al 2008.…”
Section: Discussionmentioning
confidence: 99%